Evaluation of Neutrophil Dynamics Change by Protective Effect of Tadalafil After Renal Ischemia/Reperfusion Using In Vivo Real-time Imaging. Issue 2 (27th April 2021) - Maruyama, Yuki; Araki, Motoo; Kidokoro, Kengo; Sogawa, Yuji; Yoshinaga, Kasumi; Mitsui, Yosuke; Sadahira, Takuya; Wada, Koichiro; Watanabe, Masami; Watanabe, Toyohiko; Kashihara, Naoki; Nasu, Yasutomo
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Neutrophils play a major role in ischemia/reperfusion injury (IRI) in renal transplantation and acute kidney injury. However, it has been difficult to observe changes in neutrophil dynamics over time in living mice kidney. We investigate neutrophil dynamics in IRI in living mice using novel in vivo multiphoton microscope imaging techniques and characterize the renoprotective effects of a selective phosphodiesterase 5 inhibitor, tadalafil. Methods: Wild-type and endothelial nitric oxide synthase knockout mice, a model of endothelial dysfunction, were used to establish in vivo real-time imaging in living mouse kidneys. Neutrophils were labeled green with Ly-6G monoclonal antibody, and plasma flow was labeled red with BSA. Tadalafil was administered orally 1 h before surgery. Both kidney pedicles were reperfused after 37°C warm ischemia for 45 min. Results: Our novel approach revealed that neutrophils were trapped in glomerulus within a few minutes after reperfusion. They gradually increased over time and infiltrated neutrophils were observed in the tubular lumen and peritubular capillary. The neutrophils were clearly visualized rolling on peritubular capillary plexus at 3 μm/min. The administration of tadalafil significantly reduced neutrophil influx into the glomerulus in both wild-type and endothelial nitric oxide synthase knockout mice. Reduced neutrophil infiltration in tadalafil groups, which was confirmed by flow cytometry, resulted in histopathologically decreased tubular injury. The expression of vascular cell adhesion molecule 1 and kidney injury molecule 1 was partially prevented by tadalafil. Conclusions: Use of a novel technique contributed to elucidation of neutrophil dynamics after reperfusion. Tadalafil has a potential for inhibiting neutrophil infiltration in renal IRI. Abstract :